TECHNOLOGICAL ASPECTS OF HEPATICOJEJUNOSTOMY APPLICATION IN THE TREATMENT OF MIRIZZI SYNDROME TYPE II - Bychkov, Sergey; Savelyev, Vladislav (Eastern Ukrainian Medical Journal, 2026)
The incidence of gallstone disease is increasing worldwide, along with the growing percentage of complications related not only to the disease itself but also its treatment. One of the serious complications of gallstone disease, Mirizzi syndrome, is being detected more frequently. According to the literature, Mirizzi syndrome develops in 0.3–6% of patients with various forms of gallstone disease. Surgical procedures for treating Mirizzi syndrome are highly complex and are referred to in the literature as the "trap in bile duct surgery." Surgical correction of Mirizzi syndrome and iatrogenic damage to the extrahepatic bile ducts is a significant issue in hepatobiliary surgery. Materials and Methods. The treatment outcomes of 68 patients with Mirizzi syndrome type II and 5 patients with iatrogenic damage to the hepatic duct were analyzed. In 27 patients with significant damage to the wall of the hepatic duct in Mirizzi syndrome type II (the fistula occupied more than 1/3 of the duct circumference) and complete division of the common bile duct, a hepaticojejunostomy was performed on a Roux-en-Y loop of the small intestine. In 11 patients, a hepaticojejunostomy was formed using the authors' developed technique. Results and Discussion. When performing hepaticojejunostomy using the Roux-en-Y technique with a long jejunal loop, 18.8% of patients experienced intra-abdominal bile leakage in the early postoperative period, and 6.3% developed strictures of the hepaticojejunostomy after surgery. Furthermore, a disadvantage of this technique is the exclusion of a relatively large portion of the initial small intestine segment to prevent the reflux of intestinal contents into the bile ducts. The original technique for forming the hepaticojejunostomy, proposed by the authors, allowed for the avoidance of intra-abdominal bile leakage in the early postoperative period. Additionally, no clinical manifestations of cholangitis or stricture development of the biliodigestive anastomosis were observed in the long-term follow-up. Moreover, the proposed method of hepaticojejunostomy, which performs an antireflux function, preserves up to 30 cm of the small intestine in a functionally active state, compared to the techniques previously used. Conclusions. The main surgical intervention for patients with significant destruction of the hepatic duct wall in Mirizzi syndrome type II and iatrogenic damage to the hepatic duct (complete division of the duct) should be a reconstructive operation in the form of hepaticojejunostomy using a Roux-en-Y loop of the small intestine. The technique developed for forming the hepaticojejunostomy can be considered an alternative method of reconstructive surgery. It is a safe and effective operation that expands the possibilities of surgical treatment for Mirizzi syndrome type II and iatrogenic bile duct injury.